The Reality of Change Management in The Public Administration of Education in Hail and Ways to Develop From the educational leaders’ point of view - Alshalake, Hamed Nafe Moseh (Journal of Educational and Psychological Sciences, 2020)
The research aimed to know about the reality of practicing the educational leaders for the changing management in the general administration of education in Hail region form the point view of educational leaders, and to identify the obstacles of applying the changing management for the general administration of education, and to know the suggested ways to improve the changing management in the general administration of education in hail region form the point view of educational leaders.The research problem is shown in the necessity to know the reality of practicing the changing management in the general administration of education in Hail region, where the non-recognizing it, was the problem for those who in charge of developing this administration, and their lack of ability to develop the solutions and proposals which related to the development of changing management.And to achieve the goals of the study, the researcher used the descriptive survey method, and the questionnaire was the tool to collect the data. The community of study for the workers in the educational administration in hail region from helpers, and administrations managers, and the department headmaster (males and females), and their numbers were (126). The tool of study applied to all community members through the comprehensive survey wayThe results showed that the reality of practicing the educational leaders for the changing management in the general administration of education in Hail region and it was in the (mid-level) with the arithmetic mean (3.27), and the axis (The caring of administrative contact ) came as the first one from the orders, and after that, axis (Empowering leaders to change), also (Overcoming resistance to change), and then (Raising the efficiency of leaders), and finally (Creating an appropriate environment for a change).Also, the results showed the sample of study were agree with (mid-level) on " the obstacles of applying the changing management for the general administration of education in Hail region " with the arithmetic mean (3.27), there were most important once: (Not creating jobs which are appropriate with the change management), (The lack of positive factors for the leadership), and (not having new strategies for dealing with resistance power for changing).Also, the sample of the study was found the " The suggested ways to improve the changing management in the general administration of education." (very important), with the arithmetic mean (4.44), and the most important ways from their point views are: (Identifying the strengths and weaknesses in performing the education administration), (Identifying the training needs for the changing leaders), and (Using the transparency through the changing management).The researcher recommends the necessity of caring in the administrative contact, to consider it; as the most important factors to achieve the communication between the leaderships to create the administrative change, and working to create the jobs which are appropriate with the change management at the general administration of education in Hail region, and the necessity of working to Identify the strengths and weaknesses in performing the general administration of education in Hail region.
Keywords: The changing; The resistance of change; The leadership; The educational leadership; The General Administration for learning